The Intrauterine Bigatti Shaver System: An Alternative Option for Focal Retained Products of Conception - Neveta S. V. Sutherland; Hemashree Rajesh (Case Reports in Obstetrics and Gynecology)
The management of retained products of conception (RPOC) may be medical or surgical. Surgical options include blind curettage, ultrasound guided curettage, or curettage under direct vision via hysteroscopy. The definitive management of patients presenting with retained products of conception will depend on several factors: severity of bleeding, presence of hemodynamic instability or infection, and patient preference. Optimal management of retained products of conception should result in complete evacuation of the uterine cavity while minimizing endometrial trauma. This is of utmost importance in patients with reproductive desires. We report patients with RPOC managed via hysteroscopic removal using the Bigatti Morcellator. Both patients had complete evacuation of the visualized RPOC. The purpose of this paper is to present this approach as an effective management option particularly in patients with a history of subfertility and failed blind curettage.